PROPAGATING PURITAN ISLAM IN SURAKARTA: READING THE BIOGRAPHY OF ABDULLAH THUFAIL SAPUTRA - Asif, Muhammad; Himam, Mohammad Muafi (UIN Raden Mas Said Surakarta, 2019)
Abdullah Thufail Saputra, a Pakistani-Javanese descendant, was one of the most influential figures in the spread of puritan da'wah in Solo in the 1970s and 1990s. He founded the Majlis Tafsir Al-Qur'an, which is now the largest and most massive Islamic organization in Solo. This study uses a qualitative approach. This study is complemented by essential elements such as observations, as well as in-depth interviews with some of Thufail's closest people. This study also examines some of the necessary documents, especially Thufail era brochures, MTA study recordings, and other documents. This article tries to explore Abdullah Thufail's intellectual journey, starting from his traditional educational background, changing his outlook from a traditional person to later becoming a Salafi-puritan, his missionary struggle, and how he founded and developed the MTA. This paper also discusses the struggle of MTA in accepting the sole principle of Pancasila and how MTA subsequently changed orientation after joining the New Order circle in 1984. The author also argues that the doctrine of zakat and jihad, which Thufail interpreted, became the central pillar for further MTA da'wah.